The consequences of non-adherence to medicines - Julius, Mekolle, Enongene (My University, 2022)
One of the main barriers to reaping the full benefits of prescription medications is known to be poor or non-adherence to treatment regimens. Many prescription drugs significantly lose effectiveness when patients don't follow the recommended treatment plan. Adherence problems are grave difficulties that have terrible effects on the patient and the healthcare system under discussion. Therefore, to stop the situation from getting worse, patients, healthcare professionals, and other stakeholders must work together.
Keywords: adherence; antiretrovirals; hivaids